Development and Validation of a Robust HPLC Method for Simultaneous Estimation of 5-Fluorouracil and Resveratrol and its Application in the Engineered Nanostructured Lipid Carrier - Iqubal, Mohammad K.; Kamal, Abid; Iqubal, Ashif; Imran, Mohammad; Ali, Javed; Baboota, Sanjula (Current Analytical Chemistry, 2021)
Background: 5-fluorouracil and resveratrol are the two most effective anticancer drugs. Combination therapy with these two drugs has shown promising results in cancer. The formulation containing 5-fluorouracil and resveratrol has been prepared, but no analytical method is available in the literature for their simultaneous estimation. However, several analytical methods are there for estimation of either 5-fluorouracil or resveratrol alone. Therefore, the present article is designed for the simultaneous estimation of 5-fluorouracil and resveratrol by HPLC and its application in the quantification of the drugs present in the formulated nanostructured lipid carrier (NLC). Methods: The method was developed using a C18 column (Purospher® STAR RP-18 endcapped (5 μm) Hibar® RT 250-4.6) with acetonitrile and water as the mobile phase (25:75 v/v) and estimated at 272 nm. The currently developed method was further validated by the ICH guideline Q2 (R1). Combinatorial NLC of 5-fluorouracil and resveratrol was also prepared and characterized. Results: The LOD and LOQ were 8.22 and 24.91 μg mL-1 and 6.58 and 19.93 μg mL-1, respectively. The precision was under the acceptable limits of <2% RSD. The content of 5-fluorouracil and resveratrol in NLC were found to be 99.452% and 96.421%, respectively. Conclusion: The findings showed that the developed and validated method was simple, fast, costeffective, and reproducible for the simultaneous estimation of both the drugs in the same formulation.
Keywords: simultaneous determination